Addendum to Kirwan et al. (2016, Zootaxa 4121(1): 89–94) - David, Normand; Gregory, Steven M. S.; Kirwan, Guy M.; Jobling, James A.; Steinheimer, Frank D.; Brito, Guilherme Renzo Rocha (Zootaxa, 2017)
Following the publication of Kirwan et al. (2016), it has been brought to our attention that the treatment of any possible alternative genus-group name for Parus pipra Linnaeus, 1758, when treated as monotypic, was not as self-evident to others as it was to the authors. As there is no “case law” in Zoological Nomenclature, and whatever conclusions we reached were naturally subject to our interpretation of the Code (ICZN 1999), and may not necessarily accord with the views of others, we have revisited “Pythis Viell.: Pipra leucocilla Gm.” in Boie (1826: 971) which has been viewed as an available alternative name by one correspondent (Murray Bruce in litt. June 2016).